Contributions of Nursing to the Education and Promotion of Self-Care in Patients with Intestinal Ostomy: an Integrative Review - Isadora Martins de Pereira; Taiane de Oliveira Vieira; Felipe Kohl Hemsing; Elisiane de Oliveira Machado; Rejane Silveira Campos; Tatiane Gomes da Rosa Coelho (Asy-Syifa : Journal of Science and Technology Nursing, 2026)
Purpose: To identify in the literature the contributions of nursing in the education and promotion of self-care for patients with intestinal ostomy. Methods: This study is an integrative literature review conducted between April and June 2025, using the following databases: Virtual Health Library (BVS) and PubMed. To refine the search for studies, the descriptors "ostomy", "nursing care", and "self-care" were used, combined with the Boolean operators AND and OR. The inclusion criteria were: articles related to primary studies, published between 2020 and 2025, available in national and international journals, and that addressed the guiding question. Duplicate articles, literature reviews, experience reports, editorials, articles requiring payment for open access, and studies not aligned with the aim of this review were excluded. The guiding question of the study was: What are the contributions of nursing professionals in the education and promotion of self-care for patients with intestinal ostomy? Results and Discussion: A total of 15 articles were included in this review. The studies showed that the education provided by nursing professionals in the pre- and post-operative periods has a positive impact on reducing complications, improving autonomy, and developing self-care. It was found that there are still deficiencies in providing nursing guidelines for patient preparation in the pre-operative period. The use of virtual technologies was highlighted as an important ally for continuity of care after discharge, as hospital stays are becoming increasingly shorter. Additionally, nursing care combined with psychological interventions helps in the physical, emotional, and social adaptation process for patients with intestinal ostomy. Conclusion: This study revealed that nursing plays a key role as the main facilitator of education and promotion of self-care for patients with intestinal ostomy. Nurses, by providing not only practical guidance but also psychological and emotional support, help patients adapt to their new health condition.